Analisis Metode Black-Scholes dan Monte Carlo Terhadap Penentuan Opsi Jual Eropa - Megis, Febi Fortuna; Arnellis, Arnellis (UNIVERSITAS NEGERI PADANG, 2022)
Managing the risks that will occur when investing, things that can be done by trading options. Stock options are used as a means of protection against stock price volatility. Option price calculations are performed using two methods, namely the Black-Scholes method and the Monte Carlo method. The purpose of this study is to determine the best method for determining option values. This research is basic research. The data used is the daily closing price of the pharmaceutical industry's shares in the New York Stock Exchanges (NYSE), namely Astra Zenecca and Abbott Laboratorie, the Dow Jones stock index, namely Pfizer Inc., Merck & Co Inc., and Johnson & Johnson for the period August 2022 to November 2022 with a maturity of three months. The results of the research show that the Price Absolute Error (PAE) is 18.75% or 0.1875 for the Black-Scholes method and 11.66% or 0.1166 for the Monte Carlo method, thus showing that the Monte Carlo method is more accurate than the Black-Scholes method for determining options. selling Europe.